Pola penyeliaan praktikum guru bimbingan dan kaunseling sekolah rendah / Mohd Zarawi Mat Nor - Mohd Zarawi, Mat Nor (2012)
Practicum is one of the important components in the training curriculum of the primary school Guidance and Counselling Teachers (PSGCT). The patterns of practicum supervision carried out on these teachers determines the true knowledge and skills of the primary school Guidance and Counselling teachers. The aim of this study is to explore the processes and practices of the supervisors in implementing the practicum supervision. Specifically, it provides information on how the process of practicum supervision is implemented. The study is carried out on seven Institute of the Teacher Education (ITE) lecture of supervisors of PSGCTs the source of primary data and twenty-one teacher trainees as the source of secondary data. The approach used in the research is the qualitative case study. Three methods of data collection are used, namely, observations, interviews and the related document of the theoretical research based on the Systematic Supervision Approach Model by Holloway (1995). The data are analyzed manually using the Nvivo programme. Its validity is obtained after the participants and experts have scrutinized the data. Simultaneously, the data reliability is obtained from triangulation process. The researcher also made used of audit trail, rich thick description, peer review and the Cohen Kappa analysis index. The findings of the study are categorized into four constructs which are the phases of supervision, the focus of supervision, the methods of supervision and finally its form of practice. The findings also reveal that the supervisors divide the process of supervision into three phases: the pre, the current and the post. It is also found that they focus on four supervision aspects, namely clinical, administration, program and skills in the classroom. To ensure the success of the PSGCTs supervision, four methods were used. These were the direct method, written, recording and the blend of the direct and recording methods. Subsequently, the findings also show that supervisors practise six types of personal routines which are relevant to supervision aspects and the needs of the PSGCT practicum teacher trainees. The practices or routines of supervisors when they conduct supervision are educating, counselling, role-modelling, assessing, citing exemplars and directing. The entire findings are grouped into one theme, three subthemes, 18 categories, 20 subcategories, 11 elements and two subelements. The findings reveal that there is an increase in the function and the role of practicum supervision compared to the same aspects found in the Systematic Supervision Approach Model, which also serves as the framework of theoretical research. The findings of the entire study are summarized in matrix form known as the PSGCTs Practicum Supervision Matrix. Implications of the study surface, among which are, the policy of recruiting teacher trainees, the training and courses as well as the implication on the supervisor and the counsellor educator. The researcher also put forward a suggestion that an extension of this study should be conducted to enhance the counselling practicum supervision aspects.